2019
DOI: 10.1126/science.aaw0445
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem nucleus incertus controls contextual memory formation

Abstract: Hippocampal pyramidal cells encode memory engrams, which guide adaptive behavior. Selection of engram-forming cells is regulated by somatostatin-positive dendrite-targeting interneurons, which inhibit pyramidal cells that are not required for memory formation. Here, we found that γ-aminobutyric acid (GABA)–releasing neurons of the mouse nucleus incertus (NI) selectively inhibit somatostatin-positive interneurons in the hippocampus, both monosynaptically and indirectly through the inhibition of their subcortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(127 citation statements)
references
References 81 publications
4
109
0
3
Order By: Relevance
“…The MS receives both GABAergic and glutamatergic innervations from the NI neurons 21,50 , including NMB neurons as shown here, and consists of glutamatergic, GABAergic, and cholinergic neurons. A recent study reveals that NI GABAergic neurons in mice reduces animal locomotion, reduces hippocampal theta, and control fear memory by targeting both glutamatergic and cholinergic neurons in the MS and sending collateral projections to somatostatin-positive interneurons in the hippocampus, thus make mice move slower and theta oscillations weaker 50 . Here we find that NI NMB neurons promotes locomotion, arousal, and hippocampal theta by targeting the MS and several other brain areas.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The MS receives both GABAergic and glutamatergic innervations from the NI neurons 21,50 , including NMB neurons as shown here, and consists of glutamatergic, GABAergic, and cholinergic neurons. A recent study reveals that NI GABAergic neurons in mice reduces animal locomotion, reduces hippocampal theta, and control fear memory by targeting both glutamatergic and cholinergic neurons in the MS and sending collateral projections to somatostatin-positive interneurons in the hippocampus, thus make mice move slower and theta oscillations weaker 50 . Here we find that NI NMB neurons promotes locomotion, arousal, and hippocampal theta by targeting the MS and several other brain areas.…”
Section: Discussionmentioning
confidence: 88%
“…The NI has been traditionally considered as a periventricular area for stress responses because it receives functional inputs from corticotropin-releasing factor-expressing neurons [24][25][26]50 . Indeed, a substantial number of NI NMB neurons express CRF receptors ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent neuroimaging and electrophysiological work has shown a strong, positive relationship between activity in the LC and increases in pupil size (Breton-Provencher & Sur, 2019;Joshi, Li, Kalwani, & Gold, 2016;Murphy et al, 2014). However, they also demonstrate that pupil diameter is ESTIMATES OF LC FUNCTION 36 associated with activity in other brainstem areas, including those that are near the LC (e.g., inferior colliculus, superior colliculus, nucleus incertus; e.g., Costa & Rudebeck, 2016;Joshi et al, 2016;Szőnyi et al, 2019). Efforts to use pupillometry to verify that certain voxels are within the LC have found activations throughout the brainstem, particularly in dorsal areas (near the colliculi), and particularly in oddball tasks (Murphy et al, 2014).…”
Section: Estimates Of Lc Function 35mentioning
confidence: 99%
“…Using rabies virus tracing, we also examined which brain areas modulate NI GABAergic neurons directly. We found that areas that process relevant environmental inputs, including the lateral habenula or (12).…”
Section: The Nucleus Incertus Is Rapidly Activated By Salient Sensorymentioning
confidence: 88%
“…Using cell-type-specific anatomical tracing, electron microscopic analysis, and in vitro optogenetics, we discovered that the NI selectively targets SOM-positive dendrite-targeting interneurons in the CA1 and that it establishes GABAergic inhibitory synapses on these interneurons (12). The NI also inhibits glutamatergic and cholinergic neurons in the MS that send subcortical excitatory inputs onto SOM-positive hippocampal interneurons.…”
Section: Hippocampal Dendrite-targeting Interneurons Are Inhibited Bymentioning
confidence: 99%